Balancing medicine prices and business sustainability: analyses of pharmacy costs, revenues and profit shed light on retail medicine mark-ups in rural Kyrgyzstan - Maddix Jason; Waning Brenda; Soucy Lyne (BMC, 2010)
Abstract Background Numerous not-for-profit pharmacies have been created to improve access to medicines for the poor, but many have failed due to insufficient financial planning and management. These pharmacies are not well described in health services literature despite strong demand from policy makers, implementers, and researchers. Surveys reporting unaffordable medicine prices and high mark-ups have spurred efforts to reduce medicine prices, but price reduction goals are arbitrary in the absence of information on pharmacy costs, revenues, and profit structures. Health services research is needed to develop sustainable and "reasonable" medicine price goals and strategic initiatives to reach them. Methods We utilized cost accounting methods on inventory and financial information obtained from a not-for-profit rural pharmacy network in mountainous Kyrgyzstan to quantify costs, revenues, profits and medicine mark-ups during establishment and maintenance periods (October 2004-December 2007). Results Twelve pharmacies and one warehouse were established in remote Kyrgyzstan with < US $25,000 due to governmental resource-sharing. The network operated at break-even profit, leaving little room to lower medicine prices and mark-ups. Medicine mark-ups needed for sustainability were greater than originally envisioned by network administration. In 2005, 55%, 35%, and 10% of the network's top 50 products revealed mark-ups of < 50%, 50-99% and > 100%, respectively. Annual mark-ups increased dramatically each year to cover increasing recurrent costs, and by 2007, only 19% and 46% of products revealed mark-ups of < 50% and 50-99%, respectively; while 35% of products revealed mark-ups > 100%. 2007 medicine mark-ups varied substantially across these products, ranging from 32% to 244%. Mark-ups needed to sustain private pharmacies would be even higher in the absence of government subsidies. Conclusion Pharmacy networks can be established in hard-to-reach regions with little funding using public-private partnership, resource-sharing models. Medicine prices and mark-ups must be interpreted with consideration for regional costs of business. Mark-ups vary dramatically across medicines. Some mark-ups appear "excessive" but are likely necessary for pharmacy viability. Pharmacy financial data is available in remote settings and can be used towards determination of "reasonable" medicine price goals. Health systems researchers must document the positive and negative financial experiences of pharmacy initiatives to inform future projects and advance access to medicines goals.